Psychological statistics and psychometrics using Stata - Baldwin, Scott A. (College Station, Texas Stata Press, 2019)
"Psychological statistics and psychometrics using Stata by Scott Baldwin is a complete and concise resource for students and researchers in the behavioral sciences. Professor Baldwin includes dozens of worked examples using real data to illustrate the theory and concepts. This book would be an excellent textbook for a graduate-level course in psychometrics. It is also an ideal reference for psychometricians who are new to Stata. Baldwin's primary goal in this book is to help readers become competent users of statistics. To that end, he first introduces basic statistical methods such as regression, t tests, and ANOVA. He focuses on explaining the models, how they can be used with different types of variables, and how to interpret the results. After building this foundation, Baldwin covers more advanced statistical techniques, including power-and-sample size calculations, multilevel modeling, and structural equation modeling. This book also discusses measurement concepts that are crucial in psychometrics. For instance, Baldwin explores how reliability and validity can be understood and evaluated using exploratory and confirmatory factor analysis. Baldwin includes dozens of worked examples using real data to illustrate the theory and concepts. In addition to teaching statistical topics, this book helps readers become proficient Stata users. Baldwin teaches Stata basics ranging from navigating the interface to using features for data management, descriptive statistics, and graphics. He emphasizes the need for reproducibility in data analysis; therefore, he is careful to explain how version control and do-files can be used to ensure that results are reproducible. As each statistical concept is introduced, the corresponding commands for fitting and interpreting models are demonstrated. Beyond this, readers learn how to run simulations in Stata to help them better understand the models they are fitting and other statistical concepts. This book is an excellent textbook for graduate-level courses in psychometrics. It is also an ideal reference for psychometricians and other social scientists who are new to Stata"--Publisher's website.
Introduction to Stata -- Regression with continuous predictors -- Regression with categorical and continuous predictors -- t tests and one-way ANOVA -- Factorial ANOVA -- Repeated-measures models -- Planning studies : power and sample-size calculations -- Multilevel models for cross-sectional data -- Multilevel models for longitudinal data -- Factor analysis : reliability -- Factor analysis : factorial validity -- Measurement invariance.
Includes bibliographical references (pages 429-439) and indexes.
Keywords: Stata; Psychometrics -- Computer programs; Psychometrics -- Data processing; Psychometrics; Statistics as Topic